Entrepreneurship Learning, Entrepreneurial Mindset, and Creativity in Students' Entrepreneurial Intention among Economic Education Students - Sandi Sandi; Muhammad Jafar; Romansyah Romansyah; Rahmatullah Rahmatullah; Agussalim Agussalim; Adam Rahman Suradi; Fatmawati Ramli (Journal of Economic Education and Entrepreneurship Studies, 2026)
Entrepreneurship education has become an important strategy for developing university students' entrepreneurial intention; however, the underlying mechanisms through which entrepreneurship learning and entrepreneurial mindset influence entrepreneurial intention remain insufficiently understood. This study aimed to examine the direct effects of entrepreneurship learning and entrepreneurial mindset on entrepreneurial intention, as well as the mediating role of students' creativity among Economic Education students at Universitas Muhammadiyah Bone, Indonesia. A quantitative explanatory research design with a cross-sectional survey was employed. Data were collected from 65 fifth-semester students who had completed an entrepreneurship course using a structured questionnaire based on a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results revealed that entrepreneurship learning had a significant positive effect on entrepreneurial intention (β = 0.459; p = 0.030) and students' creativity (β = 0.421; p = 0.005). Entrepreneurial mindset did not significantly influence entrepreneurial intention directly (β = −0.060; p = 0.782), but it significantly enhanced students' creativity (β = 0.572; p < 0.001). Furthermore, students' creativity significantly influenced entrepreneurial intention (β = 0.596; p = 0.003) and mediated the effects of entrepreneurship learning (β = 0.251; p = 0.049) and entrepreneurial mindset (β = 0.341; p = 0.025) on entrepreneurial intention. These findings demonstrate that creativity is a crucial psychological mechanism through which entrepreneurship learning and entrepreneurial mindset are transformed into entrepreneurial intention. Therefore, higher education institutions should integrate experiential entrepreneurship learning, creativity development, and entrepreneurial mindset enhancement to strengthen students' entrepreneurial intention and prepare graduates to contribute to sustainable regional economic development.